The problem of the scope of legal regulation of atypical forms of employment on the example of platform work – introduction to the discussion (Problem zakresu regulacji ustawowej nietypowych form zarobkowania na przykładzie zatrudnienia zewnętrznego i pracy platformowej, 2025)
The aim of this study is to introduce the reader to the issue of legal regulation of atypical forms of employment, using the example of external employment and platform work, which was the subject of the 7th National Scientific Conference in the series “Atypical Employment Relationships” organized in Łódź on December 6, 2024. by the Center for Atypical Employment Relations at the Faculty of Law and Administration, as well as the Student Forum for Atypical Employment Relations and the Regional Labor Inspectorate in Łódź. The author presents his own reflections on the challenges facing Polish legislators in the context of regulating atypical forms of gainful employment, especially those that make extensive use of modern technologies. An excellent example here is the need to implement Platform Directive 2024/2831 into the Polish legal system, which must take place by December 2, 2026.